2020
DOI: 10.3390/met10121687
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Dry-Batch Grinding in a Laboratory-Scale Ball Mill of Sn–Ta–Nb Minerals from the Penouta Mine (Spain)

Abstract: The optimization of processing plants is one of the main concerns in the mining industry, since the comminution stage, a fundamental operation, accounts for up to 70% of total energy consumption. The aim of this study was to determine the effects that ball size and mill speed exert on the milling kinetics over a wide range of particle sizes. This was done through dry milling and batch grinding tests performed on two samples from the Penouta Sn–Ta–Nb mine (Galicia, Spain), and following Austin methodology. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Two of the W ore samples were Scheelite ores, received from Barruecopardo (Spain) and Mittersill (Austria). A detailed description of Barruecopardo ore can be found in recent publications [32,33]. In the case of Mittersill, an ore description can be found in [34].…”
Section: Methodsmentioning
confidence: 99%
“…Two of the W ore samples were Scheelite ores, received from Barruecopardo (Spain) and Mittersill (Austria). A detailed description of Barruecopardo ore can be found in recent publications [32,33]. In the case of Mittersill, an ore description can be found in [34].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to above, some unique studies which can potentially contribute to meeting SDGs have been reported: e.g., analysis of grinding processes (Bu et al, 2019;2020;Krauze et al, 2021;Nava et al, 2020;Prziwara et al, 2020a;Toraman, 2013), characterization and utilization of ground products (Arsoy et al, 2017;Choi et al, 2016;Gomez et al, 2019;Guzzo et al, 2019;2020;Letelier et al, 2019;Liu et al, 2015;Makuza et al, 2021;Okazaki et al, 2022;Peltoniemi et al, 2020;Yang et al, 2021). However, the grinding mechanism considerably changes depending on the type of grinding machine, which makes it difficult to evaluate the energy efficiency using a unified standard.…”
Section: Possible Contribution Of Dry Grinding To Sdgsmentioning
confidence: 99%
“…Another contribution regarding grinding kinetics of a Ta ore was the research objective in Nava et al [2]. Some variations to classical population balance model methodologies and functional operational correlations were found among the feed size; the specific breakage rate; and the Sn, Ta, and Nb contents.…”
Section: Contributionsmentioning
confidence: 99%